1994
DOI: 10.1590/s0004-282x1994000200007
|View full text |Cite
|
Sign up to set email alerts
|

Cysticercose of the central nervous system: II. Spinal cysticercose

Abstract: The compromising of the spinal canal by cysticercus is considered infrequent, varying from 16 to 20% in relation to the brain involvement. In the spinal canal the cysticercus predominantly places in the subarachnoid space. Clinical signs in spinal cysticercosis can be caused by direct compression of the spinal cord/roots by cysticerci and by local or at distance inflammatory reactions (arachnoiditis). Another mechanism of lesion is degeneration of the spinal cord due to pachymeningitis or circulatory insuffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
7

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 65 publications
0
24
1
7
Order By: Relevance
“…b Given the rarity of these presentations, treatment was discussed based on the published literature (22,27). c Experience in the use of albendazole with methylprednisolone for treatment of retinal cysticercosis and as a presurgical treatment for intravitreal cysticercosis has been published (7) but not yet replicated.…”
Section: Ii-3mentioning
confidence: 99%
“…b Given the rarity of these presentations, treatment was discussed based on the published literature (22,27). c Experience in the use of albendazole with methylprednisolone for treatment of retinal cysticercosis and as a presurgical treatment for intravitreal cysticercosis has been published (7) but not yet replicated.…”
Section: Ii-3mentioning
confidence: 99%
“…Intradural spinal cysticercosis can be subdivided in leptomeningeal (subarachnoid) or intramedullary forms (parenchymal), and the former is more prevalent than the later. Leptomeningeal form occur in approximately 80% of cases which is assumed to result from larval migration through the ventricular system into the spinal subarachnoid space, where their movement could be assisted by gravity 3) . Queiroz et al 3,9) reported that spinal distribution of cysticerci occured as follows : 34% in the cervical; 44.5% in the thoracic; 15.5% in the lumbar; and 6% in the sacral region.…”
Section: Discussionmentioning
confidence: 99%
“…A elevada freqüência de seqüelas confirma a síndrome de HIC como a manifestação mais grave da NCC, merecendo o rótulo de forma maligna, como assinalado por Lima 20 . O envolvimento medular na NCC, embora infrequente, é também motivo de grande preocupação pois, mesmo com a extirpação de cisticercos do canal raquidiano, é freqüente a evolução para paraparesia crural como sequela 10 .…”
Section: Discussionunclassified